Enhancing Students' Competence in Mastering English Words through "Scramble" Game To the Second Grade at SMK Negeri 1 Kep. Sula - Amrin Hi Saban; Jusmin HJ Wahid; Adelia Umanahu (EDU Journal - English Department of UMMU Journal, 2022)
This research is an experimental design with nonequivalent control group designs.The objective of this research is to determine whether there is a difference in the improvement of students' English words or not. This research was conducted using two groups, namely the experimental group and the control group. The experimental group is the group that is the sample of this study, and the sample carried out by the researcher is a random sampling model, conducted at SMK Negeri 1 Kepulauan Sula for thestudents of class XI. Both groups were then given a pre-test and post-test. After that, each group was given treatment; in the experimental group the researchers applied scramble games, while the control group was taught without using scramble games. And the instrument in this research is a test sheet. The test sheet was used as an instrument and further data analysis using SPSS 16.The results showed that the pre-test value of the experiment was 36.67 and the post-test was 39.64. This shows that the experimental class did not experience a significant increase in the mastering of English words. However, the results of the T-test showed that the experimental class students' score was 105, which was higher than the control class students' scores, which was 094.